2015
DOI: 10.3109/13880209.2015.1027779
|View full text |Cite
|
Sign up to set email alerts
|

Angelica sinensispolysaccharides inhibit endothelial progenitor cell senescence through the reduction of oxidative stress and activation of the Akt/hTERT pathway

Abstract: Context: Angelica sinensis (Oliv.) Diels (Apiaceae) polysaccharides (ASP) may play a key role in anti-ischemic activity. However, the anti-atherosclerotic activity and mechanism are unknown. Objective: This study investigated the protective effects of ASP against ox-LDL-induced senescence of EPCs and explored its underlying molecular mechanisms. Materials and methods: Mononuclear cells were isolated from bone marrow (BM) of SD rats and differentiated to EPCs. EPCs were exposed to oxidized low-density lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“… 29 Additionally, ASP treatment reduced the senescence of endothelial progenitor cells by relieving OS. 31 However, the effect of ASP on oxidative injury in cardiomyocytes and mechanisms underlying this effect are unclear. H9c2 is a clonal cell line derived from BD1X rat ventricle and exhibits many of the properties of cardiac muscle, such as electrophysiology, ion channels, and receptors.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Additionally, ASP treatment reduced the senescence of endothelial progenitor cells by relieving OS. 31 However, the effect of ASP on oxidative injury in cardiomyocytes and mechanisms underlying this effect are unclear. H9c2 is a clonal cell line derived from BD1X rat ventricle and exhibits many of the properties of cardiac muscle, such as electrophysiology, ion channels, and receptors.…”
Section: Discussionmentioning
confidence: 99%
“…It possess a superior clinical efficacy and fewer side effects [14]. For example, angelica sinensis polysaccharides inhibit endothelial progenitor cell senescence through the reduction of oxidative stress and activation of the AKT/hTERT pathway [27]. And it also suppresses cell growth and cell metastasis in human lung adenocarcinoma A549 cells by regulating MMPs/TIMPs and TGF-β1 [23].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that ox-LDL also accelerated the senescence of EPCs, leading to cellular dysfunction (13,14). Lai and Liu showed that ox-LDL-induced senescence of EPCs was mediated by oxidative stress and the Akt/hTERT pathway (15).…”
Section: Introductionmentioning
confidence: 99%